OVERCOMING LEXICAL CHALLENGES IN INTERPRETING CULTURE- AND HISTORY-RICH CONTENT (KONFERENSIYA, 2025)
This extended research paper examines the full range of lexical, cultural, and historical challenges that interpreters face when working with speeches, interviews, and analytical reports rich in heritage, identity, and historical references. The study details polysemy, ambiguity, culture-bound terminology, historical registers, metaphorical complexity, ideological vocabulary, and proper names in multi-cultural contexts